The Quranic Weltanschauung (World View) and the Environment - Mohsen Nouraei (آموزه‌های قرآنی, 2013)
The environment which confronts considerable problems nowadays is one of the most important issues of men. According to the author although practical and scientific endeavors (cultivation) have been done to control this problem, it is impossible to solve it completely, except the fidelity to the high revelation teachings of the Quran. The present article which has been constructed according to a descriptive - analytic method is going to explore and analyze the verses which are inclined to the environment. These verses state the bases and fundamentals of the Quran weltanschauung in this field. The most important principles consist of the purposefulness of the environment, the balance of the environment, the aesthetics of the environment, biodiversity and mastering the environment for men. The importance of these bases depends on comprehensiveness, eternities and providing its home executive insurance for the environment laws.